Prevalence and genetic characterization of Dientamoeba fragilis in asymptomatic children attending daycare centers - Oliveira-Arbex, Ana Paula [UNESP]; David, Erica Boarato [UNESP]; Caccio, Simone Mario; Branco da Fonseca, Catia Regina [UNESP]; Martin, Joelma Gonçalves [UNESP]; Kurokawa, Cilmery Suemi [UNESP]; Tosini, Fabio; Souza-Neto, Jayme Augusto [UNESP]; Guimaraes, Semiramis [UNESP] (Inst Medicina Tropical Sao Paulo, 2021)
In order to provide additional data on the prevalence and genetic diversity of Dientantoeba fragilis in human populations, we conducted a study in children from low-income communities in Sao Paulo State. Brazil. Fecal samples from daycare center attendees up to 6 years old (n=156) and staff members (n=18) were submitted to PCR and sequencing of D. fragilis as well as to microscopic examination for the presence of other intestinal parasites. All children assessed were asymptomatic and 10.3% (16/156) were positive for D. fragilis. No worker was found to be positive. An association between Dientamoeba and coinfection with other intestinal parasites was observed. Concerning the genetic diversity, 14 and only two isolates were genotype 1 and genotype 2, respectively. Our findings outline interesting aspects: (1) asymptomatic children as carriers of Dientamoeba in communities in which environmental conditions ensure parasite transmission and. (2) association between Dientamoeba infection in young children and coinfection with other enteric parasites, reinforcing its transmission via the fecal-oral route.
Keywords: Dientamoeba fragilis; Prevalence; Children; PCR; Genotypes